Chromatin: The Final Frontier in Splicing Regulation? - Fox-Walsh, Kristi (Dev Cell, 2010)
Pre-mRNA splicing, once thought to be a strictly posttranscriptional event in gene expression, is subject to a multitiered network of regulation. Luco et al. now report in Science that this regulation seems to begin with chromatin modifications, suggesting that the histone code may be a prequel to the splicing code.